Entering the teaching profession in Slovakia - Luchenko, Olha; Yurchenko, Valeriia (H. S. Skovoroda Kharkiv National Pedagogical University, 2023)
The article studies the current state of the teacher induction process in Slovakia, namely the prerequisites for entering the teaching profession. The focus of the current research is the following: the attractiveness of the teaching profession and its influence on the decision-making of future students of pedagogical major, teacher job satisfaction level, the proportion of education requirements for subject knowledge and teaching practice, availability of the profession, the assistance in the search for open positions and vacancies, probation period as a filter to the teaching occupation. The research aims to determine the problematic aspects of the transition period from student to teacher that need to be addressed to prevent early maladjustment and drop-out in the teaching profession. Methodology. The research was carried out by applying theoretical and empirical methods. The data were obtained from novice school teachers having conducted an online survey using Google Forms with open and closed questions. The study’s preliminary results revealed the social image of the teaching profession and components of its attractiveness for future students, problems with the ratio of academic and practical parts in teacher education, possible ways to enter the profession, and the obstacles of the process. The conducted research allowed us to come to the following conclusions. As a result of the low social image of a teacher, Slovakia is facing a shortage in the profession. The substantial misbalance in initial teacher education in favor of academic knowledge and the absence of specific official requirements for practical experience has subsequences in the quality of school education and early teacher maladjustment. Implementing an open system in the teaching profession is a temporary solution that causes many concerns, especially with the introduction of short-term standard requirements in teaching abilities. Lack of career help for new graduates-teachers throughout their job hunt may cause them to leave the education field. In this situation, adequate support of novice teachers becomes necessary, and the teacher induction program is a subject for future research. У статті досліджується сучасний стан процесу входження вчителів у професію в Словаччині, а саме передумови вступу до вчительської професії. У центрі уваги даного дослідження: привабливість професії вчителя та її вплив на прийняття рішення майбутніми студентами педагогічної спеціальності, рівень задоволеності вчителя роботою, співвідношення освітніх вимог до предметних знань і педагогічної практики, доступність професії, допомога в пошуку відкритих вакансій, випробувальний термін як фільтр до вчительської діяльності. Мета дослідження – визначити проблемні аспекти перехідного періоду від студента до вчителя, на які необхідно звернути увагу, щоб запобігти ранній дезадаптації та втратам кваліфікованих кадрів у професії. Методологія. Дослідження проводилось із застосуванням теоретичних та емпіричних методів. Дані були отримані від вчителів-початківців, завдяки онлайн-опитуванню за допомогою Google Forms з відкритими та закритими питаннями. Попередні результати дослідження виявили соціальний імідж професії вчителя та складові її привабливості для майбутніх студентів, проблеми зі співвідношенням навчальної та практичної частин у педагогічній освіті, можливі шляхи входження в професію та перешкоди даного процесу. Проведене дослідження дозволило дійти наступних висновків. Через низький соціальний імідж вчителя у Словаччині очікується нестача кадрів у професії. Суттєвий дисбаланс у початковій педагогічній освіті на користь академічних знань і відсутність конкретних вимог до практичного досвіду має свої наслідки у якості шкільної освіти та ранньої дезадаптації вчителя. Запровадження відкритої системи в професії вчителя є тимчасовим рішенням, яке викликає багато занепокоєнь, особливо із запровадженням діяльності вчителів на короткий термін із низькими стандартами вимог до педагогічних вмінь. Відсутність кар’єрної підтримки випускників – майбутніх вчителів – під час пошуку роботи може призвести до того, що вони покинуть освітню галузь. У цій ситуації адекватна допомога у працевлаштуванні вчителів-початківців стає необхідною, а програма введення вчителів у професію в Словаччині є предметом наступного дослідження.
Входження у професію вчителя в Словаччині
Keywords: education requirements; initial teacher education; job satisfaction; profession attractiveness; pre-service professional orientation; Slovakia; teaching practice; вимоги до освіти; початкова педагогічна освіта; задоволеність роботою; привабливість професії; професійна орієнтація; Словаччина; педагогічна практика